Evaluation of the Emar English Series for the Second Cycle of Basic Education in Syria based on Receptive and Productive Skill (Damascus University Journal of educational and Psychologyical sciences, 2024)
The purpose of this study is to determine the extent to which receptive  and productive skills are available in the Emar English Series for the Second Cycle of Basic Education: Student's 'book and workbook. To fulfill the objective of the study, the researcher designed an evaluation checklist for productive (speaking and writing) and receptive (reading and listening) skills to identify the extent to which these skills are available in 7th, 8th, and 9th grade student's books and workbooks. The study's sample included all of the pages of a English student's book  and workbook for the seventh, eighth, and ninth grades. As a result, the six books are evaluated in terms of productive and receptive skills. The study's findings revealed that the majority of instructional and evaluative activities in the field of basic English language skills for 7th, 8th, and 9th grade student's books and workbooks are focused on reading skills, while speaking, writing, and listening skills were all found to be below average. Consequently, there is no logical balance in the distribution of basic skills in the student's book and workbook for the seventh, eighth, and ninth grades. According to the results of the receptive and productive skills, these books focused on receptive skills rather than productive skills. Productive skills are available for the 7th, 8th, and 9th grades as follows: 19.29%, 15.65%, 16.30%, whereas receptive skills are available for the 7th, 8th, and 9th grades as follows: 81.56%, 84.34%, and 83.68%.
Keywords: Receptive Skills, Productive Skills; English Textbook; Emar English Series; Second Cycle Of Basic Education